Detection of sutural diastasis in traumatic head injury: A diagnostic dilemma - Chawla, Hitesh Chawla; Tyagi, Ashish (Journal of Indian Academy of Forensic Medicine, 2021)
Following head trauma, diastasis of the cranial sutures may occur with or without skull fractures and may be the only indication of  skull damage. Axial non-contrast CT scanning is the gold standard technique for evaluating head injury. However, detection of sutural  diastasis may not be possible at normal axial views of CT scan, which can lead to dilemma in medico-legal cases. Therefore, the  present study was aimed to detect the sutural diastasis in cases of traumatic head injury brought for medico-legal postmortem  examination and comparing them with antemortem radiological evaluations. The cases of traumatic head injury that underwent  medico-legal postmortem examination during the two years were studied retrospectively. The cranial sutural separation observed in  the study subjects during autopsy was compared with the antemortem radiological investigations, which were collected from the  hospital records of the deceased. Sutural separation was detected in 5 out of 60 cases that died due to head trauma. All sutural  diastasis were extensions of linear/ depressed or comminuted skull fracture. None of the NCCT head report sutural separation, while  associated fractures were diagnosed. Medico-legal significance of sutural diastasis is akin to skull fracture. Detection of sutural  diastasis may not be possible at normal axial views of CT scan, which are routinely performed in trauma settings. Thin slices on axial  plane during CT scan with sagittal and coronal reformations can better delineate sutural diastasis. To minimize the risk of  misdiagnosis, a cautious approach in radiological diagnosis of sutural diastasis is desirable, especially in medico-legal cases.
Keywords: Head injury; Suture; Diastasis; CT scan; Autopsy; Fracture